Construction of Concave PdAg Nanoshells with Limited Thickness for Efficient Electroxidation of Ethanol - Wu, Quanlin; Zhang, Gongguo; Zhao, Na; Zheng, Yiqun; Ma, Yanyun; Liu, Feng; Liu, Maochang (Frontiers in Materials, 2021)
Noble metal nanocrystals enclosed with curved surfaces are of great benefit for applications in electrocatalysis since the atomic steps and kinks on these facets have higher chemical activity. Herein, we report the fabrication of PdAg nanoshells with tunable thickness in the range of 5-13 nm and a unique concave cubic morphology, as well as the exploration of their applications for ethanol oxidation reaction (EOR) in alkaline media. The success of current work relies on the conformal deposition of PdAg on concave Au nanocubes, where the controlled reaction kinetics and proper chosen capping agent are both crucial for the growth mode. When loaded on carbon black and working as electrocatalysts, they exhibited superb electrochemical activity (e.g., 600.21 mA mg-1 in mass activity and 19.57 A m-2 in specific activity), together with improved EOR kinetics and long-term durability, as compared to Au@Pd nanoparticles and commercial Pd/C. The current work offers a feasible strategy to produce PdAg bimetallic nanocrystals with concave surface and validates their promising application as fuel cell catalysts, which could be extended to morphology engineering of other noble-metal nanocrystals for a broad range of applications.